2015
DOI: 10.1530/eje-14-0821
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia in everyday life after gastric bypass and duodenal switch

Abstract: Design: Gastric bypass (GBP) and duodenal switch (DS) in morbid obesity are accompanied by marked metabolic improvements, particularly in glucose control. In recent years, episodes of severe late postprandial hypoglycemia have been increasingly described in GBP patients; data in DS patients are scarce. We recruited three groups of subjects; 15 GBP, 15 DS, and 15 non-operated overweight controls to examine to what extent hypoglycemia occurs in daily life. Methods: Continuous glucose monitoring (CGM) was used du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 56 publications
5
41
0
4
Order By: Relevance
“…Individuals with more severe postprandial hypoglycaemia exhibit higher postprandial insulin and GLP‐1 levels and, although the pathophysiological mechanisms are not completely understood, the exaggerated insulin and GLP‐1 responses are believed to be of great importance . Continuous glucose monitoring (CGM) has shown that hypoglycaemia is detectable in up to 75% of a population that has undergone RYGB, but is not symptomatic in all individuals . In individuals with symptoms, PBH is associated with reduced quality of life and weight regain, and PBH has been suggested to be related to the increased rate of accidental deaths seen after RYGB .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with more severe postprandial hypoglycaemia exhibit higher postprandial insulin and GLP‐1 levels and, although the pathophysiological mechanisms are not completely understood, the exaggerated insulin and GLP‐1 responses are believed to be of great importance . Continuous glucose monitoring (CGM) has shown that hypoglycaemia is detectable in up to 75% of a population that has undergone RYGB, but is not symptomatic in all individuals . In individuals with symptoms, PBH is associated with reduced quality of life and weight regain, and PBH has been suggested to be related to the increased rate of accidental deaths seen after RYGB .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Continuous glucose monitoring (CGM) has shown that hypoglycaemia is detectable in up to 75% of a population that has undergone RYGB, but is not symptomatic in all individuals. 5,6 In individuals with symptoms, PBH is associated with reduced quality of life and weight regain, and PBH has been suggested to be related to the increased rate of accidental deaths seen after RYGB. 7 Hypoglycaemic symptoms do not always correlate well with the severity of hypoglycaemia, and it is possible that rapid and large fluctuations in blood glucose levels account for some of the symptoms associated with PBH.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Abrahamsson et al. used continuous glucose monitoring to show that patients with bypass or biliopancreatic diversion spend a significant amount of time with blood glucose levels <3.3 mmol/l (60 mg/dl) (2.9 and 5.9% of the time, respectively), while only 20% of this time is accompanied by symptoms. The most intriguing study is the one by Laurenius et al.…”
Section: Mechanismsmentioning
confidence: 99%
“…The hypothesis of hypoglycaemia 'unawareness' among patients remains valid, consistent with that which has been observed in type 1 diabetes [29]; that is, biological hypoglycaemia may be considered as pathological even in the absence of symptoms recognized by the patients. Thus, Abrahamsson et al [25] used continuous glucose monitoring to show that patients with bypass or biliopancreatic diversion spend a significant amount of time with blood glucose levels <3.3 mmol/l (60 mg/dl) (2.9 and 5.9% of the time, respectively), while only 20% of this time is accompanied by symptoms. The most intriguing study is the one by Laurenius et al [26], comparing patients with a very severe clinical presentation with asymptomatic patients, which found no difference in glycaemia, plasma insulin or glucagon profiles between the patient groups.…”
Section: Mechanismsmentioning
confidence: 99%
“…In nondiabetic patients, within the 2 weeks following a RYGB, the quantity of carbohydrates (25 or 50 g in solution) and the glycemic index of the meal (mixed meal test with 37.5 g of glucose) do not impact the maximum plasma glucose [20]. Furthermore, Abrahamson et al illustrated that low glucose concentrations observed in real life were not always found under laboratory conditions (OGTT or mixed meal test) [21].…”
Section: Introductionmentioning
confidence: 99%